Global inequalities, multipolarity, and supranational organizations engagements with gender and education / Desigualdades globales, multipolaridad y compromisos de los organismos supranacionales con el asunto de género y educación - Unterhalter, Elaine (Journal of Supranational Policies of Education (JOSPOE), 2016)
ABSTRACT This paper seeks to identify the emergence of a multi-polar space regarding international development in the last ten years that stands between agendas associated with human rights and basic needs, security, the environmental agenda, and responses to the 2008 financial crisis. In this environment, gender and education, notably issues associated with girls’ access to school, have come to occupy a particular resonant space, signalling both an end to all development ills, and the dissolution of differences between, for example, the state and the private sector, equality oriented NGOs and those linked with profit. The paper discusses how in this process supra-national organisations concerned with education deploy a number of key terms –empowerment , effectiveness and evidence – and how the ambiguities associated with these allow policies concerned with gender and education to signal both a social justice project and processes which sanction or sanitise relations of commodification, exploitation or continued inequalities. The analysis comprises three threads of discussion. In setting the scene I first present a montage of some features of global inequalities associated with gender and education and some of the slippery dimensions of multi-polarity. I then consider some of the ways in which multi-polarity has been deployed in discussions of international relations and radical democracy, and use some of the metaphoric aspects of this notion to characterise the present moment in international development policy. Through this I attempt to theorise approaches to gender, education and international development that I term dispersal. In the third section I outline some of the relationships of supra-national organisations with national and local institutions working on gender and education, and show, using the example of the Department for International Development (DFID) Girls’ Education Challenge (GEC) programme how features of dispersal are evident in policy declarations, programme descriptions and framing discourses. The conclusion draws out the implications of this analysis for some of the key global policy declarations being negated in 2015, such as the Sustainable development Goals (SDGs). Key words: Education, gender, multipolarity, supranationality, inequality, mainstreaming. RESUMEN Este artículo busca identificar la emergencia de un espacio multipolar sobre desarrollo internacional en los últimos diez años que se enmarca entre agendas asociadas con los derechos humanos y las necesidades básicas, seguridad, la agenda medioambiental y respuestas a la crisis financiera de 2008. En este contexto, género y educación, temas notablemente asociados con el acceso de las niñas a la educación, han venido a ocupar un espacio notablemente resonante, señalando ambas un final a todas las enfermedades del desarrollo y la disolución de las diferencias entre, por ejemplo, el estado y el sector privado, ONGs orientadas a la igualdad y aquellas relacionadas con el lucro. El artículo aborda el tema de cómo en este proceso las organizaciones supranacionales involucradas con la educación despliegan un número de términos clave – empoderamiento, efectividad y evidencia- y cómo las ambigüedades asociadas con éstas permiten que se lleven a cabo medidas sobre género y educación para indicar ambos un proyecto de justicia social y procesos que sancionen o saneen las relaciones de comercialización, explotación y continuas desigualdades. El análisis engloba tres hilos de discusión. En la presentación del tema abordo una serie de características de desigualdades globales asociadas con el género y la educación y algunas de las dimensiones resbaladizas de la multipolaridad. A continuación, trato algunas de las formas en que la multipolaridad ha sido debatida en discusiones sobre relaciones internacionales y democracia radical; y uso algunos de los aspectos metafóricos de esta noción para caracterizar el momento presente en política internacional de desarrollo. A través de esto, intento teorizar enfoques de género, educación y desarrollo internacional que yo denomino como disperso. En la tercera sección trazo algunas de las relaciones entre los organismos supranacionales y las instituciones locales que trabajan en el tema de género y educación; y muestro, usando el ejemplo del Programa Girls’ Education Challenge (GEC) del Departamento para el Desarrollo Internacional (DFID en sus siglas en inglés) cómo las características de dispersión son evidentes en las declaraciones sobre políticas, descripciones de programas y discursos de encuadre. La conclusión dibuja las implicaciones del análisis para algunas de las declaraciones de política global habiendo sido negadas en 2015, como son los Objetivos de Desarrollo Sostenible (ODS). Palabras clave: Educación, género, multipolaridad, supranacionalidad, desigualdad, integración.